Pengaruh Pendidikan Kewirausahaan, Lingkungan Keluarga Dan Keterampilan Berwirausaha Terhadap Motivasi Berwirausaha (Studi Pada Mahasiswa Manajemen Angkatan 2019 UNiversitas Muhammadiyah Metro) - Maylana Anggraini; Ardiansyah Japlani; Durotun Nasikah (Jurnal Manajemen DIVERSIFIKASI, 2025)
With the still high Labor Force Participation Rate (TPAK) in the Lampung Province area, Muhammadiyah Metro University's class of 2019 management students themselves are felt capable of overcoming this problem, namely by increasing entrepreneurial motivation, because it is hoped that by increasing the number of entrepreneurs in Indonesia it can open new jobs, reduce unemployment rate and can also help improve the economy of the surrounding community and also the country. This research aims to find out whether entrepreneurship education, work environment and entrepreneurial skills influence entrepreneurial motivation. Meanwhile, in this research the researcher used a quantitative type of research. The population in this study was 138 management students from the class of 2019 at Muhammadiyah Metro University. Determining the number of samples using the Sovlin formula with a margin of error of 5%, obtained a sample of 102 samples. The data collection technique used was using interviews and questionnaires. Data analysis used includes validity test, reliability test, normality test, linearity test, homogeneity test and multiple linear regression analysis with the help of the SPSS version 25.0 application. Entrepreneurship education, work environment and entrepreneurial skills have a positive and significant influence on the entrepreneurial motivation of management students class of 2019 at Metro Muhammadiyah University.